Implementasi Metode SAW dalam Sistem Pendukung Keputusan untuk Seleksi Jasa Pengiriman Barang UMKM di Kota Blora - Joko Handoyo; Cevin Eris Setiawan (MEKAR : Journal Information System and Computer Application, 2025)
The rapid development of digital technology and the surge in e-commerce activities have made reliable goods delivery services a non-negotiable critical success factor for Micro, Small, and Medium Enterprises (MSMEs). However, the vast selection of logistics providers, each presenting distinct advantages and disadvantages, often leads to significant confusion for MSMEs, ultimately compromising their operational efficiency and negatively impacting customer satisfaction. Recognizing this crucial need for streamlined decision-making, this study was explicitly aimed at developing a Decision Support System (DSS) designed to provide objective, data-driven recommendations for selecting the optimal delivery service. We employed a rigorous quantitative research approach, utilizing the widely accepted Simple Additive Weighting (SAW) method for multi-criteria decision analysis. Data were meticulously collected through structured interviews with a substantial sample of 100 MSMEs located in Blora City. The subsequent analytical process systematically involved stages of data normalization, precise criteria weighting (covering aspects like cost, speed, and service quality), and accurate final ranking calculations. The empirical results definitively showed that J&T (A1) obtained the highest overall preference value of 32%, firmly establishing it as the best alternative based on the established criteria. It was closely followed by Lion Parcel (A4), TIKI (A3), and JNE (A2). This outcome strongly demonstrates that the SAW method is highly effective in generating objective, needs-tailored rankings for complex logistical choices. The study ultimately concludes that the successful implementation of this SAW-based DSS significantly improves the objectivity and efficiency of decision-making, empowering MSMEs to strategically align their logistics choices with key performance indicators like low cost, high speed, and excellent service quality, thereby demonstrably enhancing operational efficiency and expanding market reach.